Factors Affecting Company Value in Agricultural - Anam, Hairul; Kusumawati, W (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2022)
The Influence of Profitability, Company Size, Dividend Policy, Inflation, and Interest Rates on Firm Value in Plantation Subsector Agricultural Companies Listed on the Indonesia Stock Exchange for the 2015-2019 Period.This study aims to examine the effect of Profitability, Company Size, Dividend Policy, Inflation, and Interest Rates on Firm Value. The samples of this research were 6 plantation subsector agricultural companies which were listed on the stock exchangeIndonesiaselected using purposive sampling method during the 2015-2019 study. The analytical method used in this research is multiple linear regression. Based on the test results, it is concluded that profitability affects firm value, firm size affects firm value, dividend policy affects firm value, inflation affects firm value, and interest rates affect firm value.